2015
DOI: 10.1016/j.chaos.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence and symmetry of time series: Application to transition detection

Abstract: International audienceThe study of transitions in low dimensional, nonlinear dynamical systems is a complex problem for which there is not yet a simple, global numerical method able to detect chaos–chaos, chaos–periodic bifurcations and symmetry-breaking, symmetry-increasing bifurcations. We present here for the first time a general framework focusing on the symmetry concept of time series that at the same time reveals new kinds of recurrence. We propose several numerical tools based on the symmetry concept al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…However, from our point of view, only isometries (translation T , reflection R , inversion I and glide reflection G ) are suitable. This statement is supported by the recent work reported in [ 8 ] where the concept of symmetry was placed back on stage in the study of time series. Indeed, in [ 8 ], it was shown that the concept of recurrences could be generalized by taking into account the symmetry properties of m -patterns.…”
Section: Standard Fuzzy Entropy and The New Entropy Measuresupporting
confidence: 69%
See 3 more Smart Citations
“…However, from our point of view, only isometries (translation T , reflection R , inversion I and glide reflection G ) are suitable. This statement is supported by the recent work reported in [ 8 ] where the concept of symmetry was placed back on stage in the study of time series. Indeed, in [ 8 ], it was shown that the concept of recurrences could be generalized by taking into account the symmetry properties of m -patterns.…”
Section: Standard Fuzzy Entropy and The New Entropy Measuresupporting
confidence: 69%
“…This statement is supported by the recent work reported in [ 8 ] where the concept of symmetry was placed back on stage in the study of time series. Indeed, in [ 8 ], it was shown that the concept of recurrences could be generalized by taking into account the symmetry properties of m -patterns. As entropy can be derived from the recurrence concept (the recurrence plot [ 9 ] is defined as with ), from [ 8 ], four new kinds of entropy ( , , , or , , , or , , , ) can be proposed.…”
Section: Standard Fuzzy Entropy and The New Entropy Measuresupporting
confidence: 69%
See 2 more Smart Citations
“…Pham and Yan [30] proposed the sample entropy to measure Recurrence Plots irregularities. Girault [31] measured the symmetry in Recurrence Plots to identify the system's dynamic behavior. Sipers et al [32] defined a procedure for retrieving a signal from a Recurrence Plot, but their method is valid only for embedded signals.…”
Section: Introductionmentioning
confidence: 99%